Haughty and active Brazilian foreign policy to conflicts in Libya and Syria: Challenging the hegemonic siegue - Ferreyra, Matías [UNESP] (My University, 2019)
One of the pretensions in the haughty and active foreign policy of the governments of Luís Ignácio 'Lula' Da Silva and Dilma Rousseff was Brazil's involvement in the 'hegemonic structures' of the great powers, which led to the search for greater participation on the agenda of international security. The objective of this article is to analyze this pretension in Brazilian diplomacy in the face of armed conflicts in Libya and Syria, in the context of humanitarian crises heated with the Arab revolts, in 2011. The article discusses in this context, the proposals and normative resistances of Brazil, together with other emerging countries, in order to conclude that Brazil has challenged but not altered the hegemonic siege on crisis and conflict management in the Middle East.
A política externa ativa e altiva do Brasil frente aos conflitos na Líbia e na Síria: desafiando o cerco hegemônico
Keywords: Armed Conflicts; Brazil; Emerging Countries; Hegemonic Structures